DEVELOPMENT OF THE PONDOK PESANTREN TANJUNG SALAM WEBSITE IN CIWIDEY DISTRICT, BANDUNG REGENCY - Dani Rohpandi; Feri Alpiyasin; Nono Sudarsono; Heri Wahyudi; Feri Irawan; Muhamad Ma’rufi Ibnu Amir; Prastyo Pratama; Rizal Fauzi; Syaidan Ali Pratama (Politeknik Mardira Indonesia, 2025)
The development of Islamic boarding school institutions can be carried out using an internet-based information medium to be publicly accessible and certainly requires infrastructure that meets the necessary criteria. Developing a website certainly requires skills and expertise to produce information that is easily accessible, attracts attention, and can be understood by its visitors. In developing the website for Pondok Pesantren Tanjung Salam, the community service team from STMIK Mardira Indonesia uses a descriptive method with a qualitative approach and the waterfall model in software development (Software Development Life Cycle). With the development that has been carried out, training for the management, especially the operators and administrators responsible for the website's content, is of course needed. The result of this website development provides free access to information for the public.